Morphology, structure, and segmental dynamics in polyazomethine/hybrid carbon nanofillers composites. Issue 12 (19th June 2019) - Bronnikov, Sergei; Kostromin, Sergei; Asandulesa, Mihai; Podshivalov, Aleksandr; Timpu, Daniel
Abstract: The polyazomethine/hybrid carbon nanofillers composites were fabricated. The nanofilles were comprised of thermally reduced graphene oxide (rGO) and multi‐walled carbon nanotubes (MWCNTs) varying in rGO:MWCNTs ratio; the total nanofillers loading was 1 wt%. The scanning electron miscroscopy images revealed uniform distribution of the hybrid nanofillers and formation of 3D networks between rGO and MWCNTs. Molecular dynamics of the polymer chains in these nanocomposites was investigated with broadband dielectric spectroscopy. The polymer fragility, the dielectric glass transition temperature, and the dielectric relaxation strength of the nanocomposites were evaluated and analyzed depending on the rGO:MWCNTs ratio. The thermal glass transition temperature and the thermal relaxation strength evaluated from the differential scanning calorimetry data were shown to behave in other manner. This behavior was interpreted in terms of a fraction of polymer being immobilized in an interfacial layer around the nanoparticles.